2019
DOI: 10.17265/2332-7839/2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Games Body and Movement

Abstract: In the contemporary age traditional games could be a way to debate and establish a comparison of knowledge carriers to communicate methodologies of good practices adopted and experiences in the use in the protection, conservation and safeguarding of cultural heritage. Different intellectual approaches(1,2,3)defined traditional games are an expression of a country"s cultural background, beliefs and passions as well as reflect the living conditions at the time of their creation. Traditional games seem to have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…This is to say that the games offer strong nuances of togetherness and unity for the children to internalize while they play (Zayyadi et al, 2018). In the same vein, Aypay, (2016) and Palumbo et al, (2019) also reported that traditional games helped children to learn subjects like sports and also cultural values in a fun way. Likewise, traditional games improve students' cognitive in their learning activity process (Widiana et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…This is to say that the games offer strong nuances of togetherness and unity for the children to internalize while they play (Zayyadi et al, 2018). In the same vein, Aypay, (2016) and Palumbo et al, (2019) also reported that traditional games helped children to learn subjects like sports and also cultural values in a fun way. Likewise, traditional games improve students' cognitive in their learning activity process (Widiana et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Traditional games represent a country's cultural heritage, beliefs, passions, and living conditions at the time of their formation. They are based on readily accessible physical components across countries [1]. According to the United Nations Educational, Scientific, and Cultural Organization [2] traditional sports and games must be protected and promoted as sports practices and intangible cultural heritage for the future development of sports and societies because they foster intercultural and intercommunity dialogues, peace, youth empowerment, and ethical sportsmanship.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional sports games are traditional games that contain elements of sport and tradition [5]. Games are an important form of entertainment for children and adults, through which children organize independently and they have important educational significance [6]. All forms of children's play are rights for children but there are conditions that are carried out such as voluntarily, safely, the development of children for their surroundings and children can regulate their emotions [7].Traditional sports can be interpreted as a tradition that has developed over several generations, as well as in the sense of something related to the cultural traditions of a nation more broadly.…”
Section: Introductionmentioning
confidence: 99%